INVESTMENT COOPERATION OF UKRAINE AND THE COUNTRIES OF THE EUROPEAN UNION - Valerii Osetskyi; Viktoriia Kulish (Izdevnieciba "Baltija Publishing", 2018)
The article deals with the essence of investing and the evolution of views on the investment process. The essence and structure of foreign investment are determined. The position of Ukraine in the International Ratings on the level of attractiveness of the investment climate in the country is highlighted. The dynamics of inflow of foreign investments into the Ukrainian economy is shown. The volumes of attraction of direct foreign investments into the Ukrainian economy from the countries of the European Union as well as the level of export of capital from Ukraine to the countries of the Euro zone have been analyzed.